Pais de crianças público alvo da educação especial : relação entre empoderamento e habilidades sociais - Aragon, Carmelina Aparecida (Universidade Federal de São Carlos, 2017)
The way parents of disabilities children deal with day by day situations involving their children can influence the final results of their search for information and services essential to the child's development. Considering the decisive factor in child development that deals with both the empowerment of families and the repertoire of parents social skills, the purpose of the study (a) to characterize the level of empowerment and the social skills repertoire of disabilities children’s parents in child development from zero to six years of age; (b) to verify the relationship between empowerment, social skills and sociodemographic variables; (c) verify the parents' perception about the school, the services and the legal rights of the handicapped child. The Data collection took place in four distinct locations, located in three municipalities in the interior of São Paulo. The parents’ interviews were conducted individually and lasted on average 40 minutes. Twenty-nine mothers and six parents disabilities children’s or retarded child development participated in this study. To respond to the objectives the participants were evaluated according to their conceptions about the school, the services and the legislation, the level of empowerment and the repertoire of social skills. For that, were used the Questionnaire about the conception of parents - school, services and legislation, Brazil Criteria Questionnaire, the Family Empowerment Scale, and the Social Skills Inventory. The quantitative data obtained through the instruments were analyzed using descriptive statistics (measures of central tendency and dispersion). In order to relate the variables obtained through the instruments, the Spearman Posto-Order Correlation Coefficient was used. The results showed that in the case of empowerment, the factor that presented the highest average was Competence (M = 4.13), so it is possible to affirm that the participants feel that they are good parents and are confident in solving problems. However, the factor that measured the Militancy System obtained the lowest mean (M = 3.28), and the items that presented lower scores were related to aspects as to get in touch with politicians and authorities, and to give suggestions to those responsible for improvements in the services offered the children. In addition, the analysis has shown that it is not possible to state that an individual who has a good repertoire of social skills will also have a high level of empowerment. However, parents who have a good average in the factor that measured the militancy tend to be more informed parents about the services that the children receive and parents with a high level of knowledge tend to have more self-control In the face of aggressive situations. Therefore, it is possible to consider that knowing the level of empowerment and the repertoire of social skills of disabilities children’s parents is essential to think ways to work and establish possible intervention programs aimed at this public.
Disabilities children's parents target of special education : relationship between empowerment and social skills
Keywords: Educação especial; Família; Empoderamento; Habilidades sociais; Crianças; CIENCIAS HUMANAS::EDUCACAO